Geographical and temporal variation of multiple paternity in invasive mosquitofish (Gambusia holbrooki, Gambusia affinis). Issue 24 (22nd November 2019) - Gao, Jiancao; Santi, Francesco; Zhou, Linjun; Wang, Xiaoqin; Riesch, Rüdiger; Plath, Martin
Abstract: Multiple paternity (MP) increases offspring's genetic variability, which could be linked to invasive species' evolvability in novel distribution ranges. Shifts in MP can be adaptive, with greater MP in harsher/colder environments or towards the end of the reproductive season, but climate could also affect MP indirectly via its effect on reproductive life histories. We tested these hypotheses by genotyping N  = 2, 903 offspring from N  = 306 broods of two closely related livebearing fishes, Gambusia holbrooki and Gambusia affinis . We sampled pregnant females across latitudinal gradients in their invasive ranges in Europe and China, and found more sires per brood and a greater reproductive skew towards northern sampling sites. Moreover, examining monthly sampling from two G. affinis populations, we found MP rates to vary across the reproductive season in a northern Chinese, but not in a southern Chinese population. While our results confirm an increase of MP in harsher/more unpredictable environments, path analysis indicated that, in both cases, the effects of climate are likely to be indirect, mediated by altered life histories. In both species, which rank amongst the 100 most invasive species worldwide, higher MP at the northern edge of their distribution probably increases their invasive potential and favours range expansions, especially in light of the predicted temperature increases due to global climate changes.